Pengaruh SKKNI dan Kompetensi SDM terhadap Pengembangan SDM di Unit Profesi SDM dalam Menghadapi Era MEA - Mahdane, Afri; Hubeis, Musa; Kuswanto, Sadikin (Institut Pertanian Bogor, 2018)
Manpower or HR expert or professional desired by the company, then to improve the competence of human resources, the government has formulated the Indonesian National Work Competency Standards (SKKNI) in various fields one of them in the field of MSDM. SKKNI is nationally applicable as a reference for the provision of professional education and training (training), competency test and professional certification in the field of MSDM. This standard has been endorsed by the minister of labor and transmigration on September 9, 2014. SKKNI contains competencies related to HR management that are relevant to different types of business. Data collection in this research using survey method involving 51 respondents with purposive sampling technique. Data analysis in this research is done by using SEM method. The results of this study show that SKKNI has no significant effect on human resource competence and HR professional development, human resource competence has significant effect on Company Policy but human resource competence has no significant effect to HR professional development, company policy has significant effect to the development of HR profession